Improved time response of stabilization in synchronization of chaotic oscillators using mathematica - Shahzad, Mohammad; Ahmad, Israr; Saaban, Azizan; Ibrahim, Adyda (MDPI AG, 2016)
Chaotic dynamics are an interesting topic in nonlinear science that has been intensively studied during the last three decades due to its wide availability.Motivated by much researches on synchronization, the authors of this study have improved the time response of stabilization when parametrically excited Φ6—Van der Pol Oscillator (VDPO) and Φ6—Duffing Oscillator (DO) are synchronized identically as well as non-identically (with each other) using the Linear